2017
DOI: 10.1007/978-3-319-53889-1_14
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms of Gene Regulation in Amyotrophic Lateral Sclerosis

Abstract: Despite being clinically described 150 years ago, the mechanisms underlying amyotrophic lateral sclerosis (ALS) pathogenesis have not yet been fully understood. Studies in both animal models of ALS and human patients reveal a plethora of alterations such as increased glutamate-mediated excitotoxicity, redox stress, increased apoptosis, defective axonal transport, protein-misfolding events, mitochondrial impairment and sustained unregulated immune responses. Regardless of being sporadic or familiar ALS, the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 154 publications
0
33
0
2
Order By: Relevance
“…Minimotifs are the foundation of the histone code. Enzymes that covalently modify minimotifs, including those in histones, are central to AD, PD, ALS, HD, and other polyQ track expansion disorders summarized in recent reviews [258][259][260][261][262][263].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Minimotifs are the foundation of the histone code. Enzymes that covalently modify minimotifs, including those in histones, are central to AD, PD, ALS, HD, and other polyQ track expansion disorders summarized in recent reviews [258][259][260][261][262][263].…”
Section: Epigeneticsmentioning
confidence: 99%
“…The etiology of ALS remains unknown though it has been suggested that interaction between a genetic susceptibility profile and certain environmental factors may contribute to the disease through epigenetic changes . In fact, some studies have shown that ALS patients harbor specific epigenetic marks as changes in DNA methylation in the central nervous system (CNS) .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, alterations in gene expression in postmortem human samples have led to the hypothesis that correcting epigenetic abnormalities may alter pathogenesis. Moreover, class I and class II histone deacetylases (HDACs) were reported to be altered in postmortem motor cortex and spinal cord as well as in in vitro and in vivo models of ALS . However, there is a clear discord in previous reports focused on HDACs and their downstream targets in ALS.…”
mentioning
confidence: 99%
“…Previous studies have provided evidence for epigenetic dysregulation in ALS. Specifically, alterations in gene expression in postmortem human samples [5][6][7] have led to the hypothesis that correcting epigenetic abnormalities may alter pathogenesis. Moreover, class I and class II histone deacetylases (HDACs) were reported to be altered in postmortem motor cortex and spinal cord as well as in in vitro and in vivo models of ALS.…”
mentioning
confidence: 99%
See 1 more Smart Citation